2008
DOI: 10.1016/j.cell.2007.11.042
|View full text |Cite
|
Sign up to set email alerts
|

PTRF-Cavin, a Conserved Cytoplasmic Protein Required for Caveola Formation and Function

Abstract: Caveolae are abundant cell-surface organelles involved in lipid regulation and endocytosis. We used comparative proteomics to identify PTRF (also called Cav-p60, Cavin) as a putative caveolar coat protein. PTRF-Cavin selectively associates with mature caveolae at the plasma membrane but not Golgi-localized caveolin. In prostate cancer PC3 cells, and during development of zebrafish notochord, lack of PTRF-Cavin expression correlates with lack of caveolae, and caveolin resides on flat plasma membrane. Expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

48
831
3
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 668 publications
(889 citation statements)
references
References 39 publications
48
831
3
7
Order By: Relevance
“…Previous work has shown that Cavin1 is a critical structural component of caveolae (Hill et al, 2008). Knockdown of Cavin1 was performed to determine if the reorganization of Ras was a result of a specific loss of CAV1 or due to the loss of PM cholesterol levels as significant co-clustering was observed between RFP-tH and GFP-H-RasG12V after MCD treatment (Fig.…”
Section: Caveolae-dependent Reorganization Of Ras Nanoclusteringmentioning
confidence: 99%
“…Previous work has shown that Cavin1 is a critical structural component of caveolae (Hill et al, 2008). Knockdown of Cavin1 was performed to determine if the reorganization of Ras was a result of a specific loss of CAV1 or due to the loss of PM cholesterol levels as significant co-clustering was observed between RFP-tH and GFP-H-RasG12V after MCD treatment (Fig.…”
Section: Caveolae-dependent Reorganization Of Ras Nanoclusteringmentioning
confidence: 99%
“…Intriguingly, caveolae in adipocytes were suggested to produce TG (Ost et al 2005), which may also be transferred to LDs through the hemi-fusion channel. The functions of caveolins are closely linked to a family of cytoplasmic proteins termed cavins (Hill et al 2008;Bastiani et al 2009;Hansen et al 2009;McMahon et al 2009). PTRF/ cavin-1 is essential for the formation of caveolae (Hill et al 2008;Liu et al 2008) and, like caveolin, has been shown to be associated with LD function and lipid storage in cultured adipocytes (Aboulaich et al 2006), mice (Liu et al 2008), and human patients (Hayashi et al 2009;Rajab et al 2010).…”
Section: Interactions With Caveolae Caveolins and Cavinsmentioning
confidence: 99%
“…Four cavin proteins exist and they are named cavin-1 (a.k.a. polymerase I and transcript release factor, PTRF) (Hill et al, 2008;Vinten et al, 2005), cavin-2 (serum deprivation protein response, SDPR), cavin-3 (sdr-related gene product that binds to c kinase, SRBC) and cavin-4 (muscle restricted coiled-coiled protein, MURC). The cavin proteins form tissue and cell-specific complexes in the cytosol.…”
Section: Introductionmentioning
confidence: 99%